Seasonal Variations In The Fat Content Of Cow Milk Under Village Conditions Of Tamil Nadu - Singh, D. Anandha Prakash; Saravanakumar, V. Ramesh; Thiruvenkadan , A.K.; Devendran, P.; Muralidharan, J. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
In Namakkal district, 14 Tamil Nadu Co-operative Milk Producers Societies (TCMPS) were selected randomly and the data (n=16028) available at Namakkal Chilling Centre, Tamil Nadu Co-operative Milk Producers Federation (TCMPF) were used for this study. The mean milk fat percentage was generally higher in the evening milk when compared to the morning milk. The pooled overall mean fat percentage was found to be 4.42 per cent. Mohanur block recorded significantly highest milk fat per cent both in the morning and evening followed by Sendamangalam and Namakkal blocks. Maximum mean fat per cent (4.517) was observed in north-east monsoon followed by winter (4.43 per cent) and south-west monsoon (4.372 per cent). The least mean fat per cent was registered during summer (4.343 per cent) season